Biological Effects of Polysaccharides from Bovistella utriformis as Cytotoxic, Antioxidant, and Antihyperglycemic Agents: In Vitro and In Vivo Studies. - Maaloul, Aya; Pérez Manríquez, Claudia; Decara, Juan; Mari-Beffa, Manuel; Álvarez-Torres, Daniel; Latorre-Redoli, Sofía; Martínez-Albardonedo, Borja; Araya-Rojas, Marisel; Fajardo, Víctor; Abdala-Díaz, Roberto Teófilo (MDPI, 2025)
This study explores the bioactive potential of Bovistella utriformis biomass and its polysaccharides (PsBu) through comprehensive biochemical and bioactivity analyses, focusing on their antioxidant, cytotoxic, and antihyperglycemic properties. Methods: Elemental analysis determined the biomass’s chemical composi tion. Antioxidant activity was assessed using ABTS and DPPH assays. Monosaccharide composition was analyzed via gas chromatography-mass spectrometry (GC-MS). In vitro cytotoxicity assays were conducted on cancer and normal cell lines to determine IC50 values and selectivity indices (SI). Zebrafish embryo toxicity was evaluated for teratogenic effects, and an in vivo antihyperglycemic study was performed in diabetic rat models. Results: The biomass exhibited high carbon content (around 41%) and nitrogen levels, with a balanced C/N ratio nearing 5. Protein content exceeded 50%, alongside signifi cant carbohydrate, fiber, and ash levels. Antioxidant assays revealed inhibition rates of approximately 89% (ABTS) and 64% (DPPH). GC-MS analysis identified glucose as the predominant sugar (>80%), followed by galactose and mannose. Additionally, HPLC detected a photoprotective compound, potentially a mycosporin-like amino acid. Cyto toxicity assays demonstrated PsBu’s selective activity against colon, lung, and melanoma cancer cell lines (IC50: 100–500 µg·mL−1), while effects on normal cell lines were lower (IC50 > 1300 µg·mL−1 for HaCaT, >2500 µg·mL−1 for HGF-1), with SI values approaching 27, supporting PsBu’s potential as a targeted anticancer agent. Zebrafish embryo assays yielded LC50 values ranging from 1.4 to 1.8 mg·mL−1.
MDPI
Keywords: Hongos medicinales; Polisacáridos; Antioxidantes; Peces cebra - Toxicidad; Citotoxicidad por mediación celular; Hipoglucemiantes; Biomasa - Composición; Bovistella utriformis; Polysaccharides; Biomass composition; Antioxidant activity; Cytotoxicity; Selectivity index; Zebrafish toxicity; Antihyperglycemic potential; β-cell preservation